Pengaruh Vitamin C terhadap Fragilitas Osmotik Eritrosit pada Mahasiswa Kedokteran Universitas Jember yang Mengalami Stres Psikologis - Zulfahmi Muslim; Aris Prasetyo; Septa Surya Wahyudi (Pustaka Kesehatan, 2019)
Medical students are constantly getting stress that could lead to oxidative stress where the level of free radicals is higher than the level of antioxidants in the body. Free radicals can bind to erythrocyte membranes and alter membrane structure that lead to the integrity of the erythrocyte membrane resulting in decreased erythrocyte ability in preventing hemolysis. Vitamin C is an antioxidant that could prevent free radicals bond to erythrocyte membrane. Vitamin C works by donating electrons to free radicals and prevent binding to erythrocyte membranes. The purposed of this study was to determine the effect of vitamin C consumption on osmotic fragility of erythrocytes in medical students with psychological stress. This research was clinical trial research with quasi experimental with pretest-posttest control group design. Researchers used Depression Anxiety Stress Scale (DASS) questionnaire to measure the stress level. Data analysis using T test obtained mean of percentage of hemolysis between pretest and posttest was p= 0,02. It can be concluded that there is significant difference on osmotic fragility due to Vitamin C consumption in medical Student of Jember University with psychological stress.